Knowledge jobs - how to manage without burnout? - Kalimo, Raija (Scandinavian Journal of Work, Environment & Health, 1999)
The working world is progressing from the industrial era to the era of knowledge. The critical factor of success in work is shifting from machines to the human mind. All work that essentially uses and produces knowledge during and as a result of the work process can be defined as knowledge work. Knowledge jobs involve many health-promoting features, but stress and burnout may be caused by the rapid increase in the knowledge-intensity of work, new job demands, and emerging new professional subcultures emphasizing excessive commitment to work. Very little empirical evidence is available on these developments. Much more research is needed to understand the essential features of knowledge work, the change in organizational cultures, and the values guiding this process from the point of view of human resources. Research is also needed to develop organizational strategies for the prevention of stress and burnout in knowledge jobs.
Keywords: information society; job demand